Primary Malignant Giant Cell Tumor of Bone with Metastasis: A Case Report and Literature Review - Hazem Aboaid; John A deVries; Russell Gollard (Journal of Orthopaedic Case Reports)
Introduction: Malignant giant cell tumor of bone (GCTB) is a very rare tumor, especially the primary type of it. We report a case of a young female who was diagnosed with a primary malignant giant cell tumor, in addition to a literature review of the previously reported cases. This case report aims to highlight the importance of high clinical suspicion and comprehensive workup to detect malignancy in giant cell tumors. We also review and add another case to the medical literature to help better understand the behavior of this rare tumor. Case Report: A 30-year-old African American female presented with left knee pain. Imaging showed a cystic bone lesion of the left proximal tibia, which was found to be consistent with a primary malignant giant cell tumor on biopsy. She started neoadjuvant chemotherapy (methotrexate + doxorubicin + cisplatin); however, she only tolerated one cycle, and then she underwent a radical resection of the left proximal tibia with endoprosthetic reconstruction. She had multiple hospitalizations later, and she was found to have significant pulmonary and spinal metastasis. Eventually, she decided to resume chemotherapy due to her worsening disease, and she completed four cycles of doxorubicin and cisplatin with a recent plan to switch to regorafenib given her refractory disease. Conclusion: Diagnosis of primary malignant GCTB can be very challenging. It is always important to seek an expert opinion given the rare nature of this tumor. Early detection is very important to establish the appropriate treatment.